IMPLEMENTASI PRESIDENTIAL CLIMATE ACTION PLAN (PCAP) OLEH ADMINISTRASI BARACK OBAMA DALAM UPAYA MEMPERBAIKI REPUTASI AMERIKA SERIKAT DALAM NEGOSIASI IKLIM - Elizabeth Febie Gratia Milenne (2022)
This study discusses the implementation of the PCAP (Presidential Climate Action Plan) policy which aims to improve the reputation of the United States in climate negotiations. The lack of participation of the United States as one of the largest emitters of greenhouse gases in international climate negotiations has so far created a bad reputation that has led to international criticism. This then weakens the credibility and soft power of the United States on climate issues. After being passive in the international climate change regime in the past, namely the Kyoto Protocol, Barack Obama in his second period of presidency sought improvements in the current climate regime, namely the Paris Agreement. Through PCAP, the Barack Obama administration drafts domestic and foreign policies on climate issues as a priority on the political agenda. Several previous studies discussed why the United States experienced a change in the direction of climate policy under Obama, but this research focuses on discussing the direction of this change. This study uses a qualitative method with a descriptive analysis approach. The analysis technique used is data reduction, data display, and drawing conclusions. The validity of the study was determined by referential adequacy. The findings of this study are that the implementation of PCAP is not optimal so that it had not succeeded in achieving its greenhouse gas emission reduction target due to an unsupported implementation component, namely the bureaucratic structure. In this study, George C. Edward's theory of implementation was also modified by adding a component of the legislative domain, which in this case is the United States Congress as one of the determinants of the success of policy implementation.